2013
DOI: 10.1186/2049-6958-8-49
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic usefulness of pregnancy-associated plasma protein-A in suspected pulmonary embolism

Abstract: BackgroundThe role of biomarkers for prognostication and diagnosis of pulmonary embolism (PE) is increasing. It has been reported that pregnancy-associated plasma protein-A (PAPP-A) can be used as a proatherosclerotic marker. The present study was aimed to evaluate whether PAPP-A levels are helpful in the differential diagnosis of patients presenting with suspected PE.Methods53 consecutive patients evaluated for suspected PE were prospectively enrolled in the study. Serum PAPP-A levels were measured in the blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In the other study, it was shown that the serum PAPP-A level was elevated in lung cancer and it was emphasised that this increase in PAPP-A could be an inflammatory marker 33 . In contrast in another study, it was reported that there was no difference between PAPP-A levels in patients with pulmonary embolism and the control group, and there was no correlation between PAPP-A levels and inflammatory markers 34 . A study by Cengiz et al was similar to the current study and high serum PAPP-A values were determined in OSAS patients compared to a control group.…”
Section: Discussionmentioning
confidence: 75%
“…In the other study, it was shown that the serum PAPP-A level was elevated in lung cancer and it was emphasised that this increase in PAPP-A could be an inflammatory marker 33 . In contrast in another study, it was reported that there was no difference between PAPP-A levels in patients with pulmonary embolism and the control group, and there was no correlation between PAPP-A levels and inflammatory markers 34 . A study by Cengiz et al was similar to the current study and high serum PAPP-A values were determined in OSAS patients compared to a control group.…”
Section: Discussionmentioning
confidence: 75%